Determinants of the return on equity ratio (ROE) on the example of companies from metallurgy and mining sector in Poland - A. Kijewska (Metalurgija, 2016)
The purpose of this article is to present the possibilities of analyzing popular among investors ratio of ROE and identification the determinants of its growth or decline. Traditionally, according to the DuPont formula three indicators are presented as the primary determinants of ROE. The paper shows the possibility of a broader look at the issue and use of the five factors affecting the ROE. This approach reveals that, using various financial and operational strategies one can influence ROE. The analysis was conducted on the example of two Polish companies from mining and metallurgy sector.